Framework-Enhanced Electrochemiluminescence in Biosensing - Haomin Fu; Zhiyuan Xu; Hanlin Hou; Rengan Luo; Huangxian Ju; Jianping Lei (Chemosensors, 2023)
Electrochemiluminescence (ECL) has attracted increasing attention owing to its intrinsic advantages of high sensitivity, good stability, and low background. Considering the fact that framework nanocrystals such as metal–organic frameworks and covalent organic frameworks have accurate molecular structures, a series of framework-based ECL platforms are developed for decoding emission fundamentals. The integration of fluorescent ligands into frameworks significantly improves the ECL properties due to the arrangement of molecules and intramolecular electron transfer. Moreover, the various framework topologies can be easily functionalized with the recognition elements to trace the targets for signal readout. These ECL enhancement strategies lead to a series of sensitive analytical methods for protein biomarkers, DNA, small biomolecules, and cells. In this review, we summarize recent advances in various functions of frameworks during the ECL process, and constructions of framework-based ECL platforms for biosensing. The framework-based ECL nanoemitters and enhancement mechanisms show both theoretical innovation and potential applications in designing ECL biosensing systems. Perspectives are also discussed, which may give a guideline for researchers in the fields of ECL biosensing and reticular materials.